The Role of Organizational Culture, Rewards, and Leadership Models to Employee Work Commitment - Ikhsan Amar Jusman (Jurnal Multidisiplin Madani, 2022)
Employees committed to their jobs want to keep on as members of the organization. Therefore, to develop an organization, various aspects must be considered to create work commitment. The impact of organizational culture, compensation, and leadership models on work commitment is investigated in this study. This research uses multiple regression analysis to do a quantitative descriptive analysis. A simple random sample was used in this study, which included 73 employees from PT Bussan Auto Finance. The data was analysed using multiple linear regression analysis method. The results partially show that organizational culture has a significant positive effect on employee work commitment, rewards significantly affect employee work commitment, and the leadership model has a significant positive effect on employee work commitment. Simultaneously, organizational culture, rewards, and leadership models significantly affect employee work commitment.